Left behind chronic poverty in Latin America and the Caribbean - Vakis, Renos Nicos; Rigolini, Jamele; Lucchetti, Leonardo (World Bank, 2016)
Foreword -- Acknowledgements -- The roaring 2000's in Latin America and the Caribbean and the left behind -- Chronic poverty : concepts and measures -- Five facts about chronic poverty in Latin America and the Caribbean -- Drivers of chronic poverty -- From diagnosis to policies : design elements to support the chronic poor -- References -- Appendix
Includes bibliographical references
Keywords: Poverty -- Latin America; Poverty -- Caribbean Area